The relationship between helicobacter pylori infection and gastric cancer - Aziz Ari; Kenan Buyukasik (Medicine Science, 2018)
Immediately after Helicobacter pylori (H. pylori) was discovered in 1983, its relationship with upper gastrointestinal diseases has begun to be investigated. This study was carried out to investigate the relationship between H. pylori and gastric cancer by comparing the frequency of H. pylori infection between gastric cancer patients and controls. Histological results were evaluated in the diagnosis of H. pylori. This study included 60 patients who were diagnosed as gastric cancer at the Endoscopy Unit of Education and Research Hospital and were operated at the General Surgery Department of Istanbul Education and Research Hospital. The patients were questioned about major complaints and duration of these complaints, cigarette smoking and tea drinking habits, family history, and previous gastrointestinal surgery. The localization, macroscopic appearance, histology, and extent of the tumor were determined. Endoscopy, biopsy and tomography examinations were used for the localization, shape and spread of the tumor in other patients. In 40 patients undergoing resection, histological presence of H. pylori in tumor-adjacent tissue was detected in 28 (70%) patients. When all patients (60 patients) were evaluated together, H. pylori infection was detected in 40 (66.7%) patients. 40 patients undergoing resection were included in the evaluation. Although the frequency of H. pylori infection was higher in diffuse-type than in intestinal-type, this was not statistically significant. Both patients with intestinal and diffuse gastric cancers were accompanied by H.pylori infection. The rate of H.pylori infection was higher in patients with diffuse gastric cancer. Although H. pylori is one of the etiologic factors for gastric cancer, there was no significant difference in H. pylori infection between those with and without gastric cancer. [Med-Science 2018; 7(3.000): 677-80]